2013
DOI: 10.1007/s00586-013-2991-2
|View full text |Cite
|
Sign up to set email alerts
|

The combination of mesenchymal stem cells and a bone scaffold in the treatment of vertebral body defects

Abstract: MSCs in combination with a hydroxyapatite scaffold improved the repair of a model bone defect and might represent a safe and effective alternative in the treatment of vertebral bone defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
4
24
0
Order By: Relevance
“…The good manufacturing practice production of MSCs has been previously described [ 6 ]. Following State Institute for Drug Control and the Local Ethics Committee approval, nine human participants, having given informed consent, underwent a bone marrow aspiration of the anterior ilium under local anesthetic (EudraCT number 2012-005599-33 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The good manufacturing practice production of MSCs has been previously described [ 6 ]. Following State Institute for Drug Control and the Local Ethics Committee approval, nine human participants, having given informed consent, underwent a bone marrow aspiration of the anterior ilium under local anesthetic (EudraCT number 2012-005599-33 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the results of preclinical studies, hydroxyapatite and calcium phosphate are ideal substrates for use as a matrix due to their excellent osteoconductive properties [ 4 6 ]. Usually, when using hydroxyapatite, it is combined with either β -tricalcium phosphate, resulting in biphasic calcium phosphate, or biodegradable polymers, resulting in composite biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells were also used in a bone defect in the second lumbar vertebra. The defect was made by a microdrill using a ventral approach and sized 2 × 5 × 1.5 mm [206].…”
Section: Ratsmentioning
confidence: 99%
“…Both micro-CT scans and histological examinations found that the HA scaffold seeded with 5 million MSCs showed positive results compared to the others. The inflammation was negligible and the osteoinductivity was remarkably higher than that with the scaffold alone, which is evident from the increase in bone formation [ 41 ].…”
Section: Recent Advances In Skeletal Disease/injury Treatmentmentioning
confidence: 99%